Perencanaan Peta Jalur Evakuasi Mitigasi Banjir - Frans Mitran Ajami; Apriyanto A Pahrun; M. Fauzhan Algiffari (Insan Kreasi Media, 2023)
Flooding is a serious threat that often hits Libungo Village, Bone Bolango Regency. In order to improve flood risk preparedness and mitigation in this village, the purpose of this service is to plan a clear evacuation route map so as to provide the necessary guidance for villagers to be able to identify safe evacuation routes and carry out efficient evacuations when floods occur. The process of making evacuation route maps will involve collecting topographic, weather, and historical flood data. The data will be processed and analyzed and then enter the stage of the map-making process, namely field surveys to identify optimal evacuation routes. After making the map is complete, counseling is carried out to the community to provide an understanding of the use of evacuation route maps and actions to be taken when floods occur. The method used in this service is the PAR (Participatory Action Research) method, the result of this service is the level of public awareness of anticipating more severe floods. With conclusions Through mapping evacuation zones and planning clear evacuation route maps, people can better understand the steps that need to be taken in emergency situations.